A study on the reading interests of the second year, third year and fourth year students in Parada High School - Manansala, Bianca Camille A. (2009)
This study is about the reading interests of the second year, third year students in Parada High School. It aims to find out if there are significant relationship between the reading interests of the students and their academic performance as represented by their class section. It also analyzes if there are significant relationship between students' reading interest on a particular material and frequency of days spent on reading them in the library. Moreover, the frequency of library use, and the length of time spent in the library by the students are also the focus of the study.